Synthesis of Acylamino Acid Amides and Acylamino Acids by the Simultaneous Reduction and Hydrolysis of Imidazolines - Sobha, T.D.; Jirovetz, L.; Shafi, P.M. (Asian Journal of Chemistry, 2010)
Four acylamino acid amides and four acylamino acids were synthesisedby the simultaneous reduction and hydrolysis of 2-aryl-4-arylidene-2-imidazolin-5-ones (I) with a mixture of zinc dust and 5% potassiumhydroxide solution.